Enhancing adherence to asthma treatment control in children and adolescents - Anand Das Vaishnav, Venu; Patel, Ritesh (Journal of Neonatal Surgery, 2025)
To evaluate therapeutic alternatives for the stepwise treatment of asthma, including the unique requirements of this population, including the potential impacts of asthma and its therapies on growth and mental health, and caregiver participation. The study searched PubMed to discover pertinent papers, then reviewed the resulting articles, asthma management recommendations for kids, and documents from personal archives. Recent worldwide and US recommendations advocate a stepwise approach to asthma treatment for kids akin to that for people. Therapy is adjusted upward or downward, momentarily or long-term, depending on the reaction. Inhaled steroids are the preferred treatment for chronic childhood asthma, and any possible slight effects on growth are deemed negligible in comparison to their advantages. Choices for controller medication for individuals under 18 are restricted, particularly for International Initiative for Asthma Stages 2-5. Tiotropium is approved for use in the United States and Europe to treat individuals aged 6 years and older. Gradually reducing therapy, although advised yet seldom implemented, might sustain symptom management and mitigate unwanted effects while significantly lowering expenses. Patient awareness and enhanced monitoring are crucial for self-management and optimal outcomes. There is a necessity to establish specific treatment objectives for kids with asthma through step-up and step-down methodologies to optimize therapeutic advantages and mitigate possible harmful effects.